2006
DOI: 10.2527/jas.2006-055
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: Exit velocity as a measure of cattle temperament is repeatable and associated with serum concentration of cortisol in Brahman bulls1

Abstract: The objectives of this study were 1) to compare temperament assessments, using multiple techniques and over repeated observations, to gauge temperament over the long-term and 2) to evaluate the relationship of the temperament appraisals with serum concentrations of cortisol (CS). Measures of temperament were gathered over 3 repeated observations (60-d interval) of yearling, fall-born Brahman bulls (initial BW = 320 +/- 4 kg; n = 66). Temperament assessments included exit velocity (EV), which was the rate at wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
162
4
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(191 citation statements)
references
References 8 publications
23
162
4
2
Order By: Relevance
“…These results are similar to the findings of Crookshank et al (1979) and Curley et al (2006)-the more acquainted to the procedure the animal is, the less reaction they present. On the other hand, using flight speed (FS) as another tool to measure temperament, some authors found that FS increased slightly over time in both B. indicus and B. taurus cattle (Müller and von Keyserlingk, 2006;Petherick et al, 2002).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results are similar to the findings of Crookshank et al (1979) and Curley et al (2006)-the more acquainted to the procedure the animal is, the less reaction they present. On the other hand, using flight speed (FS) as another tool to measure temperament, some authors found that FS increased slightly over time in both B. indicus and B. taurus cattle (Müller and von Keyserlingk, 2006;Petherick et al, 2002).…”
Section: Discussionsupporting
confidence: 88%
“…Temperament and stress have been closely associated, and the behavior of cattle has become a method for indicating or selecting cattle that could be more stress responsive cattle or less adaptive (Curley et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Physiological responses associated with temperament can influence the probability of cows becoming pregnant because stress hormones in the bloodstream can negatively affect the release of reproductive hormones (Cooke et al, 2009). Differences in concentrations of circulating stress hormones have been associated with differences in cattle temperament (Curley et al, 2006). Cattle with "calm" temperaments had lower serum cortisol and epinephrine concentrations than animals classified as "temperamental" at a commercial feed yard (Curley et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Differences in concentrations of circulating stress hormones have been associated with differences in cattle temperament (Curley et al, 2006). Cattle with "calm" temperaments had lower serum cortisol and epinephrine concentrations than animals classified as "temperamental" at a commercial feed yard (Curley et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation